Mortgage debt and retirement transition decisions - Anderson, Somer G. (Kansas State University, 2019)
In this study, a series of logit models for discrete time were employed to investigate the association between home mortgage debt and the retirement transition decisions of older homeowners. Retirement transitions under investigation were a) the transition from the workforce to full retirement and b) the transition from full-time work to the mutually exclusive competing risks of bridge employment and full retirement. With hypotheses informed by both the STREAM framework and results from previous studies, older homeowners with home mortgage debt were expected to exit the workforce later than those without home mortgage debt. Further, a negative relationship was expected between the loan-to-value ratio and the probability of exiting the workforce in a sample of only homeowners with home mortgage debt. Data were utilized from the 2006, 2008, 2010, 2012, and 2014 waves of the Health and Retirement Study. Results from this study revealed that, holding all else equal, older homeowners with home mortgage debt are more likely to delay their exit from the workforce. Further, the results indicate that older homeowners who are male, are college graduates, and are at the lower and upper ends of the net worth spectrum are more likely to delay their withdrawal from the workforce when they carry home mortgage debt. However, homeowners with this type of debt are not necessarily more likely to engage in bridge work between periods of full-time work and full retirement. Further, results revealed that the loan-to-value ratio was not a significant contributor to the retirement transition decisions of older homeowners with home mortgage debt. Because the presence of home mortgage debt was a factor in the retirement transition decisions of older homeowners, but the degree of leverage was not, the results from this study indicate that the psychological impact of mortgage debt might be more important in retirement transition decision-making among older homeowners than the financial impact of mortgage debt. Results from this study provide the foundation for understanding the association between home mortgage debt and the retirement transition decisions among older homeowners and should be of interest to American policymakers, financial planners and educators, business organizations, and other researchers.
Keywords: Bridge Employment; Retirement Transitions; Mortgage Debt